Parathyroid autotransplantation at a novel site for better evaluation of the grafted gland function: study protocol for a prospective, randomized controlled trial - Qiuxia Cui (Trials, 2019)
Abstract Background Hypoparathyroidism is one of the most common complications encountered in thyroidectomy. In addition to parathyroid in-situ preservation, parathyroid autotransplantation (PA) is another important remedial method for patients whose parathyroid glands have been removed. However, an accurate evaluation method for the function of a transplanted parathyroid is lacking. Our preliminary study indicated that patients with PA at novel sites near antecubital veins had higher serum concentrations of parathyroid hormone (PTH). Therefore, the main hypothesis is that a grafted site closer to the cephalic vein is more useful for better evaluation of transplanted parathyroid function. This study aims to confirm the more efficient and accurate evaluation system through a prospective, randomized controlled trial. Methods In total, 280 patients will be enrolled in this study and randomly divided into two groups: 140 patients with transplanted parathyroid glands in the traditional sites (group A) and the other 140 transplanted in the novel sites (group B), close to the antecubital veins. The serum concentration of PTH and calcium ion from both forearms will be measured and monitored regularly for 12 months. The primary outcome of this trial will be the survival of grafted glands, defined as the ratio of PTH between the grafted vs. the non-grafted forearms being no less than 1.5. The secondary outcome is hypoparathyroidism, defined as the PTH level from the non-grafted forearms being less than 15 pg/ml (normal range 15–65 pg/ml). Discussion Our results from this study should provide a more accurate method to evaluate the function of transplanted parathyroid glands by comparing PTH concentrations in both the grafted and non-grafted forearms following PA at novel sites. A better PTH measurement is helpful not only for the management of postoperative patients, but also for further identification of factors affecting PA success. Trial registration ClinicalTrials.gov, ID: NCT02906748. Registered on 16 March 2016.